INTEGRASI ISLAMIC ENTREPRENEURSHIP DALAM MANAJEMEN SEKOLAH UNTUK MENINGKATKAN MUTU PENDIDIKAN DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the integration of Islamic entrepreneurship in school management and its contribution to improving the quality of primary education at SD IT Andalusia Bungo. This research employed a qualitative approach with a descriptive design. The research subjects consisted of the principal, teachers, and students selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation. Data analysis used an interactive model including data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The results revealed that the integration of Islamic entrepreneurship has been implemented through various activities such as school bazaars, honesty canteens, and contextual practice-based learning. This program not only develops students' entrepreneurial skills but also instills Islamic values such as honesty, responsibility, and social awareness. From the educational management perspective, this program reflects an innovation in school management, although it still faces limitations in structured planning and evaluation systems. The integration of Islamic entrepreneurship has positively contributed to improving the quality of education, both in the learning process and character development of students. However, further improvements are needed in management aspects, teacher competencies, and evaluation systems to ensure the program can be implemented more effectively and sustainably.